The Influence of Deviation Concept in the Structure of Architectural Form Applying Jean Cohen's Model of Deviation in Architecture - Tayib, Abdullah; Othman, Nizar Najim (Sulaimani Journal for Engineering Sciences, 2015)
The study traces the theory of Deviation (L'écart) by Jean Cohen, trying to apply it in architecture, highlighting its role in making changes in the form structure, to reach the nature of Deviations in Architecture. This study falls under the framework of shedding light on the nature of the Deviation Concept, its types and levels, and identifying its work mechanisms in language and its association with the concepts of poetics and stylistics and its manifestation in poetry, in an attempt to investigate its influence in the structure of Architectural Form . For the purpose of reaching the mechanisms of Deviation in architecture, it was necessary to study the structure of Architecture from, to understand the relationship between language grammar and architecture, concluding some important indicators for the practical part of the study, by focusing on analyzing some selected samples of Classical, Romantic, and Symbolic architecture, for the purpose of achieving the research aim on finding what corresponds to Jean Cohen's model of Deviation in architecture. The research has concluded that the mechanisms of Deviation which affect the structure of poetic language as per Cohen's model, are viable and affect the structure of architectural form, regardless the style, the movement, or the time it belongs to, and the representations of the concept were found in the classical, romantic, and symbolic architecture in varying rates, and that the semantic level or rhetorical side is one of the poetics components, which correspond to inspiration and substitutive relationships in architecture.
Keywords: Deviation; Structure of Architecture Form